Impact of railways on land use and land cover change: evidence from India - Navalkar, Aniket; Jaiswal, Sreeja; Pranadh, M.; Jayaraman, T. (Transportation research. Part D, Transport and environment, 2023)
Transport infrastructure is said to drive development in a region and affect the land use/land cover (LULC) over time. We employ a difference-in-differences (DID) framework to causally examine transport infrastructure as a driver of land use/land cover change (LUCC) using the case study of the Konkan Railway, one of the largest railway projects in post-independence India. Using multi-period multispectral satellite data, we obtained the basic LULC classes for the DID and spatio-temporal analysis. The findings suggest that the Konkan Railway led to an increase in built-up land cover and open spaces at the expense of the agricultural land cover, but did not adversely affect forest cover. This result is consistent all along the 760 km long railway. The study contributes to the emerging literature on the land use impacts of railways and underscores the importance of implementing environmental management measures.